A comparative study on PMMA-TiO2 and PMMA-ZrO2 protective coatings - Harb, Samarah V. [UNESP]; Trentin, Andressa [UNESP]; Uvida, Mayara C. [UNESP]; Magnani, Marina [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP]; Hammer, Peter [UNESP] (Elsevier, 2020)
The covalent conjugation between the phases of organic-inorganic nanocomposites and the careful tuning of the proportion of the colloidal precursors are essential to yield homogeneous, cross-linked and dense coatings that are able to protect metallic alloys against corrosion. In this work, the sol-gel route was used to prepare organic-inorganic hybrid coatings based on poly(methyl methacrylate) (PMMA) covalently bonded to TiO2 or ZrO2 nanoparticles through the coupling agent 2-hydroxyethyl methacrylate (HEMA), applied for the first time as anticorrosive coatings for metallic alloy. Different formulations of the hybrids were prepared by varying the proportion of titanium isopropoxide or zirconium propoxide, methyl methacrylate and benzoyl peroxide, and applied on carbon steel by dip-coating. The optimized parameters yielded for the two hybrids transparent and homogeneous coatings, with a thickness less than 3 μm, low surface roughness (<1.8 nm) and elevated thermal stability (>200 °C). Electrochemical impedance spectroscopy assays showed that PMMA-ZrO2 and PMMA-TiO2 coatings exhibit corrosion resistance up to 10 GΩ cm2, 7 orders of magnitude higher than the bare carbon steel, remaining essentially unchanged for PMMA-TiO2 during 14 days exposure to 3.5 % saline solution. The results suggest that PMMA-ZrO2 and PMMA-TiO2 nanocomposites are suitable for application as environmentally compliant highly efficient anticorrosive coatings.
Keywords: Corrosion protection; Functional nanocomposite; Organic-inorganic hybrid; Sol-gel process